Dynamics of the social network of young female transsexuals that live and deal with HIV/AIDS - Paula Daniella de Abreu; Ednaldo Cavalcante de Araújo; Eliane Maria Ribeiro de Vasconcelos; Vânia Pinheiro Ramos; Jefferson Wildes da Silva Moura; Zailde Carvalho dos Santos; Claudia Benedita dos Santos
ABSTRACT Objective: to analyze the social network of young female transsexuals who live with HIV/AIDS. Method: descriptive and exploratory study of qualitative approach, based on the Social Network Theory, developed in a Brazilian reference hospital for HIV/AIDS, with six transsexual women. Individual interviews were recorded and transcribed, and the data were subjected to analysis of similarities through the software program IRaMuTeQ. Results: the categories observed were: 1) dynamics of primary social network and social challenges; 2) dynamics of secondary social network and the institutional prejudice. Final considerations: the dynamics of the social network is based on the lack of support of primary and secondary networks, and the containment process limits the reach of quality of life and social emancipation. To deal with this theme will provide the visibility of young female transsexuals in confronting vulnerabilities and guaranteeing human rights.